Identifikasi Pembelajaran Literasi Finansial pada Pendidikan Anak Usia Dini - Anggraeni, Ira (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this study is to analyze and identify the existing literature on financial literacylearning in early childhood education in the Indonesian context. In this article, the researchertries to raise the concept of financial literacy learning practices which have been reluctant toinvolve children in managing finances because they are too young. This happens because thechild is considered not the time to get financial education stimulation. This study uses theliterature study method in analyzing previous studies. Based on the results of the literaturestudy, it shows that the practice of learning financial literacy is carried out through variousstrategies, namely, through the activation of the executive function. Second, it is carried outthrough an integration process into existing learning. Third, it is done through activities likesaving and saving from an early age. Fourth, the practice of financial literacy education inearly childhood education is carried out through a learning cycle. Therefore, the panel on theidentification of financial literacy learning practices can contribute both to practical needsand to the development of knowledge in the field of ECE, especially to develop financial literacylearning